(untitled) (Research, Society and Development, 2020)
The present work aims to perform the drying kinetics of adzuki beans under different drying air temperatures, to adjust mathematical models to experimental data and to determine their thermodynamic properties. Drying kinetics were performed at 40, 50, 60, 70 and 80 °C at 1.5 m/s air velocity. Parry, Page and Handerson and Pabis mathematical models were adjusted to the experimental data; The effective diffusivity, activation energy and thermodynamic properties were calculated: enthalpy, entropy and Gibbs free energy. The Page model was the best fit to the experimental drying kinetic data of adzuki beans, as it presented high values for the coefficient of determination and the lowest values for the mean square deviation; diffusivity increased with increasing drying temperature and the process presented an activation energy of 27.69 kJ/mol; From the thermodynamic properties it was possible to conclude that they were affected by the increase of the drying temperature, with reductions of enthalpy and entropy and increase of Gibbs free energy indicating a non spontaneous endergonic process.